2014
DOI: 10.14723/tmrsj.39.475
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Schottky Barrier in Low-k SiOC

Abstract: This letter discusses the reason for the tunneling behavior of zinc based oxide semiconductor thin film transistors (TFTs). The device was fabricated using SiOC as a gate dielectric, which decreased polarities depending on the combinations of oxygen and carbon ions as opposite polar sites. The threshold voltage shifts in a zinc based oxide semiconductor are presented using the metal oxide semiconductor (MOS) structure analysis of Ohmic/Schottky and Poole-Frenkel (PF) contacts based on the drain-source current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The Schottky and Ohmic contacts for semiconductors depend on the Schottky barrier, and the Ohmic contact has no potential barrier, so the current-voltage curves has linear properties. The Schottky barrier has a potential barrier and has a non-linear I-V curve, because of the depletion layer, which is due to the electron-hole combination [10][11][12]. There are many studies concerning the oxygen vacancy and structure, but the correlation between oxygen vacancy [13][14][15], structure and electronic properties remain un-researched.…”
Section: Introductionmentioning
confidence: 99%
“…The Schottky and Ohmic contacts for semiconductors depend on the Schottky barrier, and the Ohmic contact has no potential barrier, so the current-voltage curves has linear properties. The Schottky barrier has a potential barrier and has a non-linear I-V curve, because of the depletion layer, which is due to the electron-hole combination [10][11][12]. There are many studies concerning the oxygen vacancy and structure, but the correlation between oxygen vacancy [13][14][15], structure and electronic properties remain un-researched.…”
Section: Introductionmentioning
confidence: 99%
“…All of the samples showed the broad PL spectra of 350 nm∼800 nm with a main peak of 460 nm, and the full width half maximum (FWHM) of PL of SiOC and ZnS/SiOC was lower than that of ZnS. The intense PL emission peak confirms the good optical property of ZnS/SiOC, so this indicates that the optical characteristic of ZnS was improved by using SiOC due to the low surface energy and the decrease of a contact resistance at an interface between ZnS and SiOC [9,10]. in Figure 3(a).…”
Section: Resultsmentioning
confidence: 92%
“…The thin film transistors with channel materials such as ZnS, IGZO, and AZO were usually showed as the unipolar transfer characteristics [3][4][5][6][7][8], but it was reported that ZnO thin film transistor that used SiOC as a gate insulator had bidirectional ambipolar properties. SiOC became low dielectric constant with lowering the polarity, which helps to have good chemical and physical properties for high electrical quality [9][10][11][12][13][14][15]. Some factors which include the interactions between ZnO and SiOC phases and the strong adsorption to the substrate at the ZnO/SiOC surface are responsible for the improvement of performance [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, an etched multilayer mask has much higher mask efficiency than an absorber mask. 10) In order to explain the simulation results of Fig. 2, we performed an exact mathematical analysis of the propagation of electromagnetic waves inside the absorber mask structure of Fig.…”
Section: Waveguide Effect At Very Small Feature Sizementioning
confidence: 99%